Comparison of coated-platelet levels in patients with essential thrombocythemia with and without hydroxyurea treatment. (September 2013) - Reményi, Gyula; Szász, Róbert; Debreceni, Ildikó Beke; Szarvas, Mariann; Batár, Péter; Nagy, Béla; Kappelmayer, János; Udvardy, Miklós
<x xml:space="preserve">Abstract</x> Essential thrombocythemia (ET) is an acquired myeloproliferative disorder with sustained increase of platelet count. This disease may be associated with thrombotic or bleeding complications due to the altered number and function of platelets. Coated-platelets produced by a simultaneous activation of collagen and thrombin represent a subpopulation of activated platelets with high prothombinase activity and the retention of several α-granule-derived coagulation factors on their surface. There is a growing body of evidence for a relationship between variable levels of coated-platelets and different hemostatic alterations. However, no data are available on coated-platelet formation in the pathogenesis of ET in the presence or absence of treatment. The levels of coated-platelets in 43 ET patients (15 non-treated and 28 hydroxyurea-treated) without known thrombotic or hemorrhagic complications were analyzed using flow cytometry. These results were compared with data of 31 healthy individuals. In addition, platelet function was analyzed with PFA-100 analysis, and P-selectin (CD62) positivity was also measured by flow cytometry. Increased P-selectin expression was detected with prolonged PFA-100 closure times in the ET group; however, significantly lower levels of coated-platelets were found in non-treated ET patients compared to controls (23.1 ± 8.8% vs. 37.6 ± 12.7%, p = 0.0008). This tendency was more evident in patients with JAK2-V617F mutation. Patients on hydroxyurea treatment had elevated coated-platelet levels (34.1 ± 12.3%) close to the normal value. In conclusion, lower than normal levels of coated-platelets were generated in ET, which were significantly (p = 0.0008) increased by hydroxyurea treatment. We suppose that abnormal coated-platelet level may also contribute to platelet dysfunction in ET.